The role of IL-6 in thyroid eye disease: an update on emerging treatments - Murdock, Jennifer; Nguyen, John; Hurtgen, Brady J.; Andorfer, Cathy; Walsh, John; Lin, Andrea; Tubbs, Christopher; Erickson, Kristine; Cockerham, Kimberly (Frontiers in Ophthalmology, 2025)
Elevated serum interleukin-6 (IL-6) levels have been shown to correlate with disease activity in patients with thyroid eye disease (TED), a complex, heterogeneous, autoimmune disease affecting thousands of people worldwide. IL-6 plays a pivotal role in the pathogenesis of TED through three key mechanisms that together may contribute to inflammation, tissue expansion, remodeling, and fibrosis within the orbit. First, IL-6 drives an autoimmune response targeting the thyroid-stimulating hormone receptor (TSHR) by promoting the production of autoantibodies (i.e. TSHR-Ab, TSI), thereby triggering TSHR-dependent immune pathways. Second, IL-6 stimulates the activation and differentiation of orbital fibroblasts, which contributes to the inflammatory process and increase adipogenesis. Finally, IL-6 stimulates T-cell–mediated inflammation, amplifying the immune response within orbital tissues. Although corticosteroids and surgery have served as mainstays of TED treatment, a multimodal approach is often required due to the disease’s heterogeneous presentation and response to current treatment options. TED is a chronic, lifelong condition characterized by periods of exacerbation and remission, with inflammation playing a central role in disease progression and severity. Because inflammation can flare intermittently throughout a patient’s life, there is growing interest in targeting specific components of the immune system to reduce disease activity and severity. This review focuses on the current evidence supporting IL-6 as a key mediator of TED pathogenesis and explores its potential as a diagnostic biomarker and therapeutic target of the disease.